2014
DOI: 10.1016/j.solmat.2013.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromic iridium oxide films: Compatibility with propionic acid, potassium hydroxide, and lithium perchlorate in propylene carbonate

Abstract: Porous thin films of Ir oxide were prepared by reactive dc magnetron sputtering onto unheated substrates. The crystallite size was ~5 nm, and a small amount of unoxidized Ir was present. The electrochromic performance was studied by optical transmittance measurements and cyclic voltammetry applied to films in aqueous and non-aqueous electrolytes, specifically being 1M propionic acid, 1M potassium hydroxide (KOH), and 1M lithium perchlorate in propylene carbonate (Li-PC). Cyclic voltammetry measurements indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Subsequent amounts of charge insertion and extraction differ by a constant value of ~1.4 mC/cm 2 after the fourth CV cycle, and these amounts decline monotonically upon extended voltammetric cycling, which points at irreversible electrochemical reactions leading to continuous sample degradation. We note that no similar effect was found for CV cycling in the 2.0 -4.7 V vs Li/Li + range for our earlier study of Iroxide-based films [74]. The overall shapes of the curves are similar to those in Fig.…”
Section: Nickel Oxide Films In Li-pc: Electrochemical Optical and Stsupporting
confidence: 71%
See 2 more Smart Citations
“…Subsequent amounts of charge insertion and extraction differ by a constant value of ~1.4 mC/cm 2 after the fourth CV cycle, and these amounts decline monotonically upon extended voltammetric cycling, which points at irreversible electrochemical reactions leading to continuous sample degradation. We note that no similar effect was found for CV cycling in the 2.0 -4.7 V vs Li/Li + range for our earlier study of Iroxide-based films [74]. The overall shapes of the curves are similar to those in Fig.…”
Section: Nickel Oxide Films In Li-pc: Electrochemical Optical and Stsupporting
confidence: 71%
“…V vs Li/Li + which, importantly, was chosen to be the same as in our earlier investigation of Ir oxide films [74]. The voltage sweep rate was 10 mV/s, except for studies of long-term cycling durability when it was 50 mV/s.…”
Section: Elemental Compositions and Atomic Concentrations Were Determmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Thus we surmise that the increased charge density in the latter film is due to a contribution from Ir occurring primarily below 2.7 V. Enhanced charge density becomes even more pronounced for still larger Ir contents in the films (not shown). Optical transmittance spectra revealed that the optical modulation (T bleached -T colored )…”
mentioning
confidence: 72%
“…Transition metals based on metal-organic complex multicolor electrochromic materials exhibit attractive properties, such as high stability and chemiluminescence. 16 However, the expense and scarcity of the precious metals, such as ruthenium, 15,16 osmium 17 and iridium, 18 limit their practical applications. Polymeric multicolor electrochromic materials with different electrochromic activation units [19][20][21] possess the advantages of easy processing, diverse resources and facile color tunability.…”
Section: Introductionmentioning
confidence: 99%